An isolated, bright cusp aurora at Saturn. Issue 6 (13th June 2017) - Kinrade, J.; Badman, S. V.; Bunce, E. J.; Tao, C.; Provan, G.; Cowley, S. W. H.; Grocott, A.; Gray, R. L.; Grodent, D.; Kimura, T.; Nichols, J. D.; Arridge, C. S.; et al.
Abstract: Saturn's dayside aurora displays a number of morphological features poleward of the main emission region. We present an unusual morphology captured by the Hubble Space Telescope on 14 June 2014 (day 165), where for 2 h, Saturn's FUV aurora faded almost entirely, with the exception of a distinct emission spot at high latitude. The spot remained fixed in local time between 10 and 15 LT and moved poleward to a minimum colatitude of ~4°. It was bright and persistent, displaying intensities of up to 49 kR over a lifetime of 2 h. Interestingly, the spot constituted the entirety of the northern auroral emission, with no emissions present at any other local time—including Saturn's characteristic dawn arc, the complete absence of which is rarely observed. Solar wind parameters from propagation models, together with a Cassini magnetopause crossing and solar wind encounter, indicate that Saturn's magnetosphere was likely to have been embedded in a rarefaction region, resulting in an expanded magnetosphere configuration during the interval. We infer that the spot was sustained by reconnection either poleward of the cusp or at low latitudes under a strong component of interplanetary magnetic field transverse to the solar wind flow. The subsequent poleward motion could then arise from either reconfiguration of successive open field lines across the polar cap or convection of newly opened field lines. We also consider the possible modulation of the feature by planetary period rotating current systems. Key Points: Saturn's dawn arc auroral emission was observed to fade strongly for several hours This may have been attributable to reduced plasma flow shear during a prolonged solar wind rarefaction An isolated auroral spot emission is evidence of dayside reconnection at an expanded magnetosphere